Analisis Empiris terhadap Putusan Pengadilan Agama tentang Dispensasi Perkawinan Anak dalam Perspektif Pluralisme Hukum dan Maqāṣid al-Syarī'ah: Empirical Analysis of Religious Court Decisions on Marriage Dispensations for Minors from the Perspective of Legal Pluralism and Maqāṣid al-Syarī’ah - Nurbaeti; Kurniati; Musyfikah Ilyas (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
The phenomenon of granting marriage dispensations in Indonesia demonstrates a complex interaction between Islamic law, state law, and socio-cultural norms. This study aims to assess the consistency of the application of maqāṣid al-syarī'ah in decisions on child marriage dispensations in several Religious Courts in Indonesia, particularly in relation to the extent to which judges consider comprehensive child protection aspects. Using a qualitative method based on a normative juridical approach, this study analyzes four Religious Court decisions, namely PA Palembang No. 139/Pdt.P/2023/PA.PLG, PA Samarinda No. 335/Pdt.P/2021/PA. Smd, PA Samarinda No.148/Pdt.P/2023/PA.Smd, and PA Sengkang No. 1/Pdt.P/2020/PA.Skg, using the framework of legal pluralism  and maqāṣid al-Syarī’ah. The findings show that the judges' decisions in the four cases varied in terms of the balance between state law, religious values, and child protection. Social, cultural, and moral factors remain the main drivers in granting dispensations. However, from the perspective of maqāṣid al-Syarī’ah, most decisions still place ḥifẓ al-nasl and ḥifẓ al-'irḍ as the main basis for granting dispensations, especially to avoid social stigma resulting from pregnancy outside of marriage. while more fundamental considerations such as ḥifẓ al-nafs and ḥifẓ al-'aql, which include physical health, psychological readiness, and the child's education, have not been applied consistently. Only Samarinda Religious Court Decision No. 335 displays a more comprehensive use of maqāṣid. Based on these findings, this study recommends more operational technical guidelines so that the application of maqāṣid al-syarī'ah is not partial, but functions as a comprehensive child protection instrument in the context of Indonesian legal pluralism.